2018
DOI: 10.1111/scd.12334
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the effectiveness of a custom‐made toothbrush in maintaining oral hygiene and gingival health in cerebral palsy patients

Abstract: Aim:To evaluate and compare the efficacy of customized toothbrushes in maintenance of oral hygiene and gingival health with that of conventional toothbrushes in children with cerebral palsy. Methods:Thirty patients with cerebral palsy in the age group of 6 to 18 years were randomly divided into two groups-group I (normal toothbrush) and group II (customized toothbrush). Common oral hygiene instructions were given to both the groups. Before beginning the study, plaque index (PI) and modified gingival index (MGI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
6
1
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 24 publications
1
6
1
1
Order By: Relevance
“…et al [25] stated that there is significant improvement in plaque levels and gingival health of C.P. children whereas Rai T. et al [26] contradicted to our study that in individuals with cerebral palsy the efficiency of maintaining oral hygiene and gingival health increased only with custom-made tooth brushes. The plaque index for the children whose oral prophylaxis were not done, increases at 3 months in all except for H.I.…”
Section: Discussioncontrasting
confidence: 88%
“…et al [25] stated that there is significant improvement in plaque levels and gingival health of C.P. children whereas Rai T. et al [26] contradicted to our study that in individuals with cerebral palsy the efficiency of maintaining oral hygiene and gingival health increased only with custom-made tooth brushes. The plaque index for the children whose oral prophylaxis were not done, increases at 3 months in all except for H.I.…”
Section: Discussioncontrasting
confidence: 88%
“…However, it should be noted that the conclusions of case-reports could not be applied directly in clinical practice (Hurd 2014). Although a low number of interventional studies were observed (3.01%), an increased number of publications on the theme of this study was observed every decade (Abd-Elmonem et al 2021, Rai et al 2018, M Baeder et al 2017, Inal et al 2017, Yitzhak et al 2017, Feng et al 2007.…”
Section: Discussionmentioning
confidence: 85%
“…However, a review concluded evidence of only a small Hawthorne effect in randomized clinical trials (RCTs) 27 . In other studies, a less than 10% reduction in the modified gingival index (MGI) 28,29 and PlI 30,31 was observed in a manual toothbrush group after two or three weeks 32 . As a consequence, the results in this study are convincing even after the deduction of the Hawthorne effect.…”
Section: Discussionmentioning
confidence: 46%